A mini review focused on the proangiogenic role of silicate ions released from silicon-containing biomaterials. (11th May 2017) - Dashnyam, Khandmaa; El-Fiqi, Ahmed; Buitrago, Jennifer O; Perez, Roman A; Knowles, Jonathan C; Kim, Hae-Won
Angiogenesis is considered an important issue in the development of biomaterials for the successful regeneration of tissues including bone. While growth factors are commonly used with biomaterials to promote angiogenesis, some ions released from biomaterials can also contribute to angiogenic events. Many silica-based biomaterials have been widely used for the repair and regeneration of tissues, mainly hard tissues such as bone and tooth structure. They have shown excellent performance in bone formation by stimulating angiogenesis. The release of silicate and others (Co and Cu ions) has therefore been implicated to play critical roles in the angiogenesis process. In this short review, we highlight the in vitro and in vivo findings of angiogenesis (and the related bone formation) stimulated by the various types of silicon-containing biomaterials where silicate ions released might play essential roles. We discuss further the possible molecular mechanisms underlying in the ion-induced angiogenic events.